Reconstruction of Legal Protection for The Notary in Criminal Proceedings: An Analysis of the Harmonization of the UUJN and the National Criminal Code - Daddy Ramdhan; Gunawan Djajaputra (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
The criminalization of the Notary profession in Indonesia shows a worrying trend, where civil disputes are often forcibly dragged into the criminal realm. This study aims to analyze the limits of notary liability and its legal protection when designated as a suspect within the framework of legal harmonization between the Notary Position Act (UUJN) and the National Criminal Code (KUHP). The research method used is normative legal research with a statutory and case approach. The results indicate that the determination of suspect status for Notaries often ignores the nature of formal job responsibility. A reconstruction of norms is needed to synchronize the authority of the Notary Honorary Council with criminal procedural law to ensure legal certainty for public officials.